Consumers' acceptance on Islamic home financing : empirical evidence on Bai Bithaman Ajil(BBA) in Malaysia. - Abdul Razak, Dzuljastri; Mohamed, Mustafa Omar; Md Taib, Fauziah (IIUM Press, 2011)
Bai Bithamall Ajil (BBA) is the most predominant mode of home financing in Malaysia since the introduction ofIslamic banking in 1983. The BBA is a deferred installment sale where bank capitalizes on its profit up front in the sale of property. The concept is similar to debt financing which is often resulted in high cost.The BBA as practiced in Malaysia is seen not to be in compliant with the Shariah principle as the bank does not take the risk of ownership and liability of the property. Given the controversial features of the BBA, it is anticipated that there was high level of dissatisfaction among the present and potential BBA customers, including Muslims and the NonMuslims. Based on a survey of 300 owners and potential house owners, there was high level of dissatisfaction among customers, as evidenced by their low intention to use the BBA. Muslim customers in general are concerned about the features ofBBA notably its compliance with Shariah as well as its inability to fulfill the broad objective ofjustice, equality and societal well being. The Non-Muslim customers however, seem to have greater beliefs in BBA and its ability to fulfill socially desirable objectives. The discontent feelings signal the urgent need by the bankers to come up with altematives of Islamic home financing product. lvfusharakah Aflltallaqisah or the Diminishing Partnership concept has been proposed to replace BBA for its esteemed features